Leveraging the Industrial Collaboration Program for Malaysia's Aerospace Industry - Abu Bakar, Mohd Zamri; Jaafar, Jefiena; Muhamed, Ariff Azly; Rahman, Azlin Abdul; Rasedee, Ahmad Fadly Nurullah (Advances in Social Sciences Research Journal, 2024)
The Industrial Collaboration Program (ICP) in Malaysia serves as a pivotal strategy for economic growth, technological advancement and aligning to propel Malaysia towards a high-income knowledge-based economy. The objective of this study is to examine the present strategic efforts of Malaysia's Industrial Collaboratives Program in the context of the country's aerospace industry. The study specifically focus on the development of a knowledge based economy, the establishment of a global supply chain, and the creation of employment opportunities. It offers a comprehensive comprehension of the industry's potential and the crucial significance of partnership between the government and the industry. Preliminary findings indicate that the ICP has significantly contributed to skill development, technology upgrades, and has spurred research and development (R&D) activities in other key sectors such as automotive, and electronics. The study emphasizes the importance of strategic planning, robust governance, and continuous improvement to maximize the ICP's benefits specifically within Malaysia aerospace ecosystem.